Calcium and Trace Elemental Ratios of Late Triassic-Early Jurassic Carbonate Platforms (Mount Sparagio) - Ashley Prow-Fleischer; Clara L Blättler; Jordan Todes; Preston C Kemeny; Simona Todaro; Tianchen He; Bas van der Schootbrugge; Jonathan L Payne (PANGAEA, 2025)
Calcium isotope ratios (δ44Ca) and minor/trace elemental ratios (Mn, Sr, U, V, Cr, Fe /(Ca + Mg)) were measured from bulk carbonate powders in 2023 on samples collected in 2006 from an outcropping near Val Adrara, Lombardy Basin in the Italian Alps region using MC-ICP-MS at University of Chicago. Samples were collected with rock hammers and chemical measurements were performed on samples at an average resolution of 15 m. These deposits represent a shallow carbonate platform active during the Late Triassic (Rhaetian stage, ~199.7 Ma) to Early Jurassic (Hettangian stage, ~196.5 Ma)(van der Schootbrugge, 2008,doi:10.1029/2007GC001914). Carbon (δ13C), oxygen (δ18O), calcium (δ44Ca) isotope and minor/trace elemental ratios (Mn, Sr, U, V, Cr, Fe /(Ca + Mg)) were also measured in 2023 from samples collected from an outcrop near Mount Sparagio, Sicily in 2022. Carbon and oxygen isotope ratios were measured on a Finnigan MAT 253 mass spectrometer. Chemical analyses were performed at a resolution of approximately 5 m. These deposits represent a transitional to evaporitic setting during the Late Triassic (Rhaetian stage, exact dates uncertain) to Early Jurassic (Hettangian stage) (Todaro et al., 2022; doi:10.3389/feart.2022.875466). These analyses were performed to investigate potential differences in diagenetic alteration at the two sites, Val Adrara and Mount Sparagio, across the Triassic-Jurassic transition. The data is associated with the publication Prow-Fleischer et al., (2025), doi:10.1016/j.chemgeo.2024.122530.